Evaluation of Main Research and Science Production Strategies in Technical - Engineering Discipline (Field) - Reza Mehdi; Mohammad Yamani dozi sorkhabi; Zahra Sabbaghian; Hassan Fatemi; Ali akbar Mottahedi (آموزش مهندسی ایران, 2009)
With the increasing importance of science and knowledge in national development and excellence, it is vital to compile and enforce science production strategies to the utilization of potentials and advantages of knowledge and technology. Obviously, it is not possible to achieve and promote science production strategies (with taking into consideration the internal and external variable factors and their effectiveness in actual situations) without continual evaluation and disciplinary and carefully evaluated intervention. Implementation and evaluation are significant elements of planning process. Better implementation and more careful evaluation will result with more learning. In this article, main research and science production strategies for technical-engineering discipline (field) is evaluated based on a field study with two approaches of strategy-making process (indirect) and test and evaluation of criteria (direct). Based on the research results, status of science production strategies in technical-engineering discipline is estimated to be average and not encouraging. This dictates more efforts and commitment for upgrading the research and science production strategies status in aspects of design, management, implementation, monitoring and promotion.